PELANGGARAN HAK ATAS MEREK DAN MEKANISME PENYELESAIANNYA DI INDONESIA - Aryani, Esti (Wacana Hukum, 2011)
Abstract : Trademark is an important part on trading and business. Trademark right need to be protected. There are several mechanism of the dispute settlement, namely civil law mechanism, penal law mechanism, arbitration mechanism and dispute settlement alternative mechanism. Keywords: trademark right protection